Technology Transfer Challenges in Indonesia: An Experience from Industry Turbine Overhaul - Soekarno, Subiakto; Maya Damayanti, Sylviana; Samsu Wibowo, Putri Maharani (The Asian Journal of Technology Management (AJTM), 2009)
This paper discusses the problems and challenges that Indonesia faces in the process of its technology transfer. Matters discussed in this paper are based on the lead writer’s personal observation and experience of the technology transfer taking place in Indonesia’s turbine maintenance and overhaul industry.The first challenge faced is the lack of basic skills on the part of factory workers. The next challenge is the lack of supporting industries. Furthermore, the low level of English proficiency of the workforce has contribution to the technology transfer problems. Final challenges are the low credibility of the government entities that oversee the turbine maintenance industry in Indonesia. The steps undertaken in the technology transfer in the turbine maintenance and overhaul industry in Indonesia is done through several complex stages.Keywords: challenges in the transfer of technology, technology transfer in Indonesia, turbine maintenance and overhaul industry.